Why powerful buyers finance suppliers' R&D - Werner Bönte; Lars Wiethaus (University of Wuppertal, Schumpeter School of Business and Economics, 2008)
It is a common concern that pricing pressure by powerful buyers discourages suppliers' R&D investments. Employing a simple monopsonist - competitive upstream industry - framework, this paper qualifies this view in two respects. First, the monopsonist has an incentive to subsidize upstream R&D which yields more upstream R&D and higher profits in both industries than the monopsonist's commitment to higher prices. Secondly, in the presence of intra-industry R&D spillovers between upstream firms, the monopsonist has an even stronger incentive to finance upstream R&D. If the monopsonist finances more than fifty percent of suppliers R&D efforts, R&D investments in upstream industry will be higher than in the case of buyer competition.
urn:nbn:de:hbz:468-20080514
Keywords: O31; O32; L13; L20; 330; Vertical Relationships; Monopsony; Buyer Power; R&D; Knowledge Spillovers; Nachfragemacht; Monopson; Lieferanten-Kunden-Beziehung; Industrielle Forschung; Lieferant; Wissenstransfer; Ökonomischer Anreiz; Theorie